Minimal prevalence of Huntington’s disease in the South of Brazil and instability of the expanded CAG tract during intergenerational transmissions - Castilhos,Raphael Machado de (2019)
Abstract Huntington’s disease (HD) is due to dominant expansions of the CAG repeat of the HTT gene. Meiotic instability of the (CAG)n might impact the disorder frequency. We report on HD minimal prevalence in Rio Grande do Sul (RS) state, Brazil, and on intergenerational instability of the (CAG)n in HD families. Symptomatic and at-risk subjects from 179 HD families were ascertained between 2013 and 2016. Clinical, molecular and family history data were obtained. Expanded (CAG)n length differences between parent and child (delta-expanded-(CAG)n) were calculated. Effect of parental age on the (CAG)n instability upon transmission was inferred by correlating delta-expanded-(CAG)n between siblings to their age differences. HD minimal prevalence in RS state was estimated as 1.85:100,000 inhabitants. Alleles with (CAG)27-35 were found on 21/384 non-disease associated chromosomes (5.5%); among 253 expanded alleles, four (1.6%) were within reduced penetrance range with (CAG)36-39. In 32 direct transmissions, mean instability was larger among paternal than maternal transmissions. In direct transmissions and in 51 sibling pairs, parental age at the time of child birth were not correlated with delta-expanded-(CAG)n. Briefly, HD prevalence in RS state was lower than those reported for European populations. Expanded (CAG)n transmissions were unstable and not associated to parental age.